Design and Development of a Website-Based Library Information System at Valentine High School - Lianjus Obrai Sitio (Journal Majelis Paspama, 2025)
Advances in information technology provide great opportunities to improve the effectiveness of data management in various fields, including school libraries. This study aims to design and develop a website-based library information system at Valentine High School as a solution to the manual system that has been used so far. Data collection methods were carried out through observation, interviews, and documentation to obtain relevant information related to system requirements. The developed system includes features such as login, user data management, book data, categories, shelves, borrowing, returns, fines, and membership card printing. The system implementation uses software such as Adobe Dreamweaver CS5 and XAMPP, with minimal hardware support of a Dual Core computer and 4 GB of RAM. The results of the study show that a website-based library information system can speed up the service process, improve data accuracy, facilitate information storage and presentation, and reduce errors that often occur in manual systems. Thus, this system can be an effective solution in improving the quality of library services at Valentine High School.